Filsafat menjadi Alternatif Pencegah Kerusakan Lingkungan - Hardiansyah Hardiansyah (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Man destructs and exploits nature and environment without or with giving attention to the hurt or broken body of earth. Man is not wise toward nature and environment. Does Philosophy could prevent the destructions, as it serves man to become wise? Since philosophy turn away from earthly life, the world then hesitates to consult to philosophy in solving urgent problems. Basically, phi- losophy and ecology serve cooperation that results a strong relation between knowledge and philosophy in this century. Philosophy as an alternative will not rule out knowledge and religion roles. However, they are always in dialog. Like a cycles, there is a need to each other support and logic explanation and cooperation in facing life problems. The Ecology’s wisdom that is found in local wisdom, ascetics of knowledge, and philosophy’s ethic are useful to be alternatives to prevent nature and environment from destruction.